Enlarge Coal Air Duct to Improve Operational Reliability of Pulverizer System - Abidin, Muhammad As’ad; Akbar M., Muhammad (Riviera Publishing, 2026)
The coal feeder of our company's pulverizing system adopts JGC-30 weighing metering coal feeder. The raw coal in the raw coal hopper falls onto the coal feeder belt through the coal drop port by its own gravity. The existing design of high belt skirt on both sides is 60mm. A small amount of coal blocks falls off on both sides of the belt during the falling process. Due to the wind force of the coal feeder sealing wind and the operation of the belt, a small amount of coal blocks are scattered and stuck at the coal feeder weighing device. The inaccurate coal quantity measurement leads to large fluctuations in the coal feeding quantity of the pulverizing system, that will makes inducing abnormal vibration of the coal mill, insufficient coal powder output, large amount of slag discharge from the coal mill and other problems, which seriously affect the safe and stable operation of the pulverizing system. In this regard, the coal feeding belt was modified, and the skirts on both sides of the coal feeder were increased to 100mm. After the modification, it can be ensured that the raw coal does not fall from the skirts on both sides during the operation of the coal feeder, thereby solving the problem of inaccurate coal quantity measurement caused by coal blocks stuck in the weighing device.